Inovasi Kolaboratif: Menciptakan Ruang Pendanaan Untuk Luaran Penelitian Mahasiswa - Cecep Nuryadin; Cinde Adia Diningsih; Neng Wina Risky Agustin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to explore how collaborative innovation can create a funding space that serves to strengthen the research and innovation culture of students in higher education. Data were collec ted through indepth interviews, document studies, and participant observation to obtain a comprehensive picture of the dynamics of collaborative funding. The results show that collaborative funding spaces not only provide financial support but also strengthen students' motivation, academic networks, and innovative orientation. Students who receive funding support tend to produce more varied research outputs, ranging from publications and prototypes to simple patents, and are more actively involved in national and international scientific forums. Furthermore, multi-stakeholder involvement has been shown to increase the relevance of student research to the needs of society and industry. This study concludes that collaborative funding plays a role as a catalyst for the creation of a sustainable and competitive student research ecosystem. The recommendations put forward are the need for a more structured, integrative, & sustain ability-oriented collaborative funding model, with strong synergy between academia, government, industry, and the community.